Correlation of Surface and Underwater Position Fixing Techniques - Milne, P. H. (The International Hydrographic Review, 2015)
Underwater acoustic position-fixing systems developed rapidly in the 1970’s to meet the demand for more precise offshore survey work in connection with the development of North Sea oil. However the accuracy of an underwater position-fix depends on the correlation of the surface and underwater navigation systems employed, and the precise deployment of the seabed transponders. It is thus important to study the multipath propagation of the acoustic signals to limit range errors. To assist offshore operators involved in diver or submersible tracking in the vicinity of offshore structures, the problems of platform navigation and surveying have been fully researched and a system developed for the precise orientation of a diver or submersible during a platform survey. The presently developed deepwater position-fixing system is based on a stand-alone desktop mini-computer which will accept up to seven data inputs including the underwater acoustic slant ranges for subsequent evaluation to give an underwater position-fix in three dimensions (3D). The software has been designed principally for underwater navigation, and surveying, but will also accept surface radio position-fixing signals, thus saving initial set-up time as only one computational system is required. The results of underwater surveys are presented.